Cyberbullying and its associated factors among junior high school students in Hue city - Nguyen, Thi Bich No; Nguyen, Hoang Thuy Linh (Tạp chí Y Dược Huế, 2024)
Introduction: The rapid and widespread use of the Internet has created a foundation for the increase in cyberbullying behaviors among school-age children. Hence, comprehensive understanding factors influencing cyberbullying will contribute towards future health policy to improve adolescent health. Objectives: To describe the prevalence of being cyberbullying and its related factors among junior high school in Hue city. Methods: A cross-sectional study was conducted in 1082 junior high school students in Hue City in November 2022. Students participated in self-fulfilling out a prepared set of questions that included information on subject matter characteristics, Internet usage characteristics, family, living environment, and school issues, and used a cyberbullying scale to assess the prevalence of being cyberbullying. Logistics regression models were performed to identify the potential determinants of being cyberbullying. Results: The prevalence of being cyberbullying among junior high school in Hue city were 28.4%. The most common form of cyber-bullying is being made up, being gossiped about things that are not true online or over the phone (56.0%). Logistics regression analysis revealed that female (OR = 1.38; 95%CI: 1.02 - 1.89), level of being beaten by relatives from time to time or more (OR = 1.89; 95% CI:1.32 - 2.74), school bullying (OR = 4.49; 95% CI:3.18-6.36), Internet addiction (OR = 2.63; 95% CI: 1.64 - 4.24), having friends who are members of a school gang group (OR = 1.60; 95% CI: 1.13 - 2.30), that living area also occurs fight and quarels (OR = 1.41; 95% CI: 1.02 - 1.97), this area has many social catastrophes (OR = 1.62; 95% CI:1.20 - 2.20), playing with friends in the neighborhood who commit acts of catching others (OR = 1.72; 95%CI: 1.11 - 2.67) significantly associated with being cyberbullying. Conclusion: The prevalence of cyberbullying and its detrimental effects on students highlight the importance of collaboration between parents and schools. This can involve implementing strategies to promote responsible and fostering open communication to ensure students use the internet safely and constructively